ANT COLONY SYSTEM WITH MEDIAN BASED PARTITIONINGFOR IMAGE SEGMENTATION AND CLASSIFICATION - Altaei, Mohammed; Hamad, Azhar; Ali, Marwa (Iraqi Journal of Science, 2024)
The motivation we address in this paper is to find out a generic method used tosegment and classify different types of conceptual images. A novel median basedmethod was proposed as primary stage for image segmentation, in which the image ispartitioned into fixed sized quadrants called kernels. The size of kernels in a specificimage is determined according to the spectral uniformity measurements. Later, AntColony Optimization (ACO) is used to find out the optimal number of classes may existin the image, and then classify the image in terms of the determined classes. Differenttypes of images with different semantic concepts were used to test the proposedclassification method. The results obtained by ACP ensure the success of the proposedmethod and the effective performance of classification.